Current status of Aceh jernang (Daemonorops sp.) and its traditional conservation efforts. Issue 1 (March 2020) - Andini, R; Ismullah, F; Bakri, S; Sulaiman, M I; Anhar, A
Abstract: Dragon's blood or 'jernang' (in Indonesian language) is referred to the deep and bright red resin obtained from the seeds of rattan palm ( Daemonorops ). Three species of this genus, i.e. D. draco (Willd.) Blume, D. didymophilla and D. Micracantha, are highly value commodity due to their larger fruits and longer fructescences. Dragon's blood has been known in the traditional ancient Chinese medicines as haemostatic agent, antidiarrheal, antiulcer, antimicrobial and anti-inflammatory. Particularly the dracorhodin, a valuable bioactive substance, is closely associated with antitumour and wound healing activity and other industrial need. The distribution of Daemonorops is limited to Malaysia, Thailand and western Indonesia, especially in Sumatra. Harvesting D. draco seeds has been served as traditional livelihood for some local tribes and farmers in Aceh Province. Resin extracted from Aceh jernang is classified as excellent due to higher content of dracorhodin, but its processing method is still conducted in a very traditional way. The forests in Aceh are suitable for jernang to thrive, but jernang population is decreasing due to deforestation and inappropriate harvesting. Unless conservation efforts are done, jernang might extinct in the near future. Over the past few years, some local farmers have realized the importance of jernang in their livelihoods, and hence they take part in the conservation. This paper dealt with the efforts between a local jernang company, CV Draco Industrial Agribusiness (DIA Group), with Unsyiah in the traditional jernang conservation program.